2005
DOI: 10.1073/pnas.0502978102
|View full text |Cite
|
Sign up to set email alerts
|

Sumoylation induced by the Arf tumor suppressor: A p53-independent function

Abstract: The mouse p19 Arf protein has both p53-dependent and p53-independent tumor-suppressive activities. Arf triggers sumoylation of many cellular proteins, including Mdm2 and nucleophosmin (NPM͞ B23), with which p19 Arf physically interacts in vivo, and this occurs equally well in cells expressing or lacking functional p53. In an Arf-null NIH 3T3 cell derivative (MT-Arf cells) engineered to reexpress an Arf transgene driven by a zinc-inducible metallothionein promoter, sumoylation of endogenous Mdm2 and NPM protein… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
135
1
3

Year Published

2006
2006
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 119 publications
(145 citation statements)
references
References 48 publications
6
135
1
3
Order By: Relevance
“…In addition to protein binding, NPM localization is regulated by posttranslational modifications such as ubiquitinylation and sumoylation. 22,36 Therefore, another possible mechanism by which RelA may cause its relocalization is by facilitating modulation of its post-transcriptional modification state. In support of this suggestion, we found that aspirin and GFP-NoLS RelA expression induced modified (high molecular weight) forms of NPM in the cytoplasm (data not shown).…”
Section: Discussionmentioning
confidence: 99%
“…In addition to protein binding, NPM localization is regulated by posttranslational modifications such as ubiquitinylation and sumoylation. 22,36 Therefore, another possible mechanism by which RelA may cause its relocalization is by facilitating modulation of its post-transcriptional modification state. In support of this suggestion, we found that aspirin and GFP-NoLS RelA expression induced modified (high molecular weight) forms of NPM in the cytoplasm (data not shown).…”
Section: Discussionmentioning
confidence: 99%
“…Npm1 heterozygosity accelerates oncogenesis both in vitro and in vivo, supporting the fact that it has tumorsuppressive activity (16). Moreover, accumulating evidence indicates that B23 contributes to the growth-suppressing pathways through its interaction with Arf (8,17).…”
mentioning
confidence: 89%
“…Recently, it has been shown that B23 is sumoylated at only one site in Arf-null NIH 3T3 cells. Its sumoylation is increased on Arf induction, and multisumoylated species are detected (17). However, the sumoylation residues are unknown, and the physiological functions of this event remain elusive as well.…”
mentioning
confidence: 99%
“…In the Mdm2-null cell, ARF can activate the p53 through binding and inhibiting ARF-BP1/Mule, a newly identified E3 ubiquitin ligase for p53 (Chen et al, 2005). Moreover, increasing number of studies are providing evidence that ARF has p53-independent functions (Weber et al, 2000;Tago et al, 2005;Ha et al, 2007).…”
Section: Introductionmentioning
confidence: 99%